Scattering Model for Stray Light Calculations in Laser Interferometry Application to TianQin Science Interferometer. (1st March 2023) - Yan, Haoyu; Chen, Qinfang; Wang, Hu; Wang, Xingyan; Ma, Zhanpeng
Abstract: In the field of space optics, correct estimation of the amount of stray light is necessary to evaluate system performance and guide the selection of the correct design. Given the noise target of several picometers on distance measurements, this configuration is very sensitive to stray-light noise; thus, stray-light estimation is an important part of the design process. For complex optical systems, stray-light simulations can be performed by using specific optical analysis software (FRED, Tracepro, ASAP), which require expensive licenses and excessive computing time. Herein, we consider the effects of combined roughness, mirror contamination, and surface imperfections, construct a unified physical scattering model and simulate it. According to the analysis, the stray light of the telescope system is less than 10 10 of the outgoing laser power.These considerations apply to various optical systems.